THE PURPOSE OF LEGAL REMEDIES IN ADMINISTRATIVE DISPUTES - Dimitrijević, Predrag; Milenković, Nevena (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2020)
The importance of the legally defined goals of the administrative dispute for the realization of the administration legality principle as an elementary requirement for the "rule of law" - a key postulate of any democratically organized society, especially in constellation with the tendency of intensive and unstoppable expansion of administration, is constantly growing. The objectives of an administrative dispute (administrative-judicial protection) are clearly defined in Article 1 of the Law on Administrative Disputes. The Constitution recognizes and insist on importance of legality of the administrative action, especially when it decides, in the form of individual acts, about the rights, obligations and legally based interests of individuals. Starting, on the one hand, from their indisputable importance (contribution) to the realization of the already mentioned goals, and on the other hand, from the relevance of this issue in the midst of extensive reforms of public administration and administrative justice, the purpose of our doctoral dissertation research is to provide a studious, critical and bold analysis of legal remedies in an administrative dispute in order to, bearing in mind the completely realistically achievable potentials of legal remedies, contribute to the improvement of the goals that inspired their administrativeprocedural existentialism. Finally, the ultimate goal of the dissertation is to offer de lege solutions for regulation of the legal remedy package in an administrative dispute which would eliminate the drawbacks discovered in the research.